The Effect of Storage Conditions on Pasteurised Kenaf Seeds Milk Mh8234 Physiochemical Properties - Abdul Fattah Ab Razak, Mohd Zahid Abidin, Mohd Shahril Osman, Mohd Hafsanjani Salleh, Mohd Syafiq Abdullah, Farah Syahirah Abdul Shukri, Nurhayatie Sajali, Ashraf A. Razak, Mohamad Saiful Sulaiman (Mathematical Statistician and Engineering Applications, 2023)
Pasteurised kenaf seeds milk MH8234 (PKSM) has been produced from kenaf seeds which are considered waste in agricultural practices. Furthermore, studies on the effect of storage conditions on PKSM physicochemical properties have yet to be explored. Therefore, this study focused on identifying the effect of storage conditions at two different temperatures (ambient temperature (AT) 27 oC ± 2 oC and chilled temperature (CT) 4 oC ± 2 oC) for 30 days on the physicochemical properties (colour difference, emulsion stability index, viscosity, total soluble solids, turbidity and size index). This study showed that both storage temperatures and period significantly (p<0.05) affect all tested PKSM’s physicochemical properties. This condition is due to the nature of the PKSM, which seeks to achieve thermodynamic stability and component hydrolysis reaction.